Lichen extracts as raw materials in perfumery. Part 2: treemoss - Joulain, Daniel; Tabacchi, Raffaele (My University, 2009)
This is a comprehensive review of extracts from the lichen Pseudevernia furfuracea (treemoss) that are used in the fragrance industry. Qualitative and quantitative analytical aspects are critically reviewed and the results are compared to those of the related oakmoss extracts. It is shown that more than 90 constituents have been identified so far in treemoss extracts, including 42 depsides, depsidones or depside-derived compounds, and 42 triterpenes or steroids. Constituents of certain host trees, mainly Pinus species, generate specific analytical and toxicological issues which need to be considered in addition to those related to the known degradation products of lichen compounds. A new classification of lichen extracts used as raw materials in fragrance compounding is proposed.
Keywords: Pseudevernia furfuracea; treemoss; fragrances; depsides; triterpenes; steroids; resin acids; contact allergy